Twofold C−H Activation Enables Synthesis of a Diazacoronene‐Type Fluorophore with Near Infrared Emission Through Isosteric Replacement. Issue 8 (19th January 2021) - Greßies, Steffen; Ito, Masato; Sakai, Mika; Osaki, Hiroshi; Kim, Ju Hyun; Gensch, Tobias; Daniliuc, Constantin; Ando, Naoki; Yamaguchi, Shigehiro; Glorius, Frank
Abstract: The synthesis and photophysical properties of a soluble amide‐embedded coronene is reported. The key step in this synthesis is the twofold C−H activation of diazaperylene by a rhodium(III)Cp* catalyst. This unprecedented structural motif shows intense fluorescence in the near infrared region with a small Stokes shift and a distinct vibronic structure, which exhibits a slight extent of negative solvatochromism. Comparison of this compound with some relevant compounds revealed the importance of the amide incorporation in the peripheral concave region including an angular position to retain high aromaticity reflecting that of parent coronene. Treatment of this compound with Lewis acid B(C6 F5 )3 formed a bis‐adduct, which exhibited enhanced aromaticity as a consequence of the increased double bond character of the amide C−N bonds. Abstract : Twofold C−H activation of diazaperylene by a rhodium catalyst produces a bis(amide)‐embedded coronene, which retains high aromaticity and exhibits an intense near infrared fluorescence with a high quantum yield. Thus, the replacement of C=C double bonds with amides represents a useful strategy for emissive polycyclic aromatic hydrocarbons (PAH). Further complexation with B(C6 F5 )3 enhances the aromaticity of the amide‐embedded hexagon rings.